2018
DOI: 10.2166/ws.2018.127
|View full text |Cite
|
Sign up to set email alerts
|

Sorption of Ni(II) on surface of bed grains used in iron and manganese removal filters

Abstract: This paper reports the results of determinations of crystalline phase type, specific surface area, point of zero charge pH (pHpzc), and Ni(II) sorption capacities of beds for groundwater treatment. Bed materials from iron and manganese removal filters (FeRF, MnRF) as well as a catalytic bed (G1) were investigated. The reference material was MnO2-coated quartz sand (MnQS). The efficiency of Ni(II) sorption was investigated as a function of pH. It was found that the naturally formed coating on FeRF was character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…It is known from other sources that Pyrolox contains ramsdellite, nsutite, and pyrolusite [204]. The specific surface area is not large: G-1 16.5 m 2 /g [144], Gabon manganese ore 7.25 m 2 /g [194], Pyrolox 2.58 m 2 /g [204].…”
Section: Commercial Media Characteristicmentioning
confidence: 98%
See 4 more Smart Citations
“…It is known from other sources that Pyrolox contains ramsdellite, nsutite, and pyrolusite [204]. The specific surface area is not large: G-1 16.5 m 2 /g [144], Gabon manganese ore 7.25 m 2 /g [194], Pyrolox 2.58 m 2 /g [204].…”
Section: Commercial Media Characteristicmentioning
confidence: 98%
“…Comparing adsorption capacities of coated filter media is also difficult because, although it significantly depends on the amount of oxide on the carrier grain and the size of the specific surface area, it is most often expressed in terms of the unit weight of the whole composite material. In chemically coated filter media, the carrier dominates quantitatively over the coating and it has been shown that for this type of materials it is better to compare adsorption capacity in terms of unitary value of specific surface area [144]. Bruins et al [145] considered this need when comparing filter media of varying density and proposed a reference to the unitary volume of material.…”
Section: Adsorption Propertiesmentioning
confidence: 99%
See 3 more Smart Citations